GABA-induced uncoupling of GABA/benzodiazepine site interactions is associated with increased phosphorylation of the GABAA receptor - Gutiérrez, María Laura (2014)
The use-dependent regulation of the GABAA receptor occurs under physiological, pathological, and pharmacological conditions. Tolerance induced by prolonged administration of benzodiazepines is associated with changes in GABAA receptor function. Chronic exposure of neurons to GABA for 48 hr induces a downregulation of the GABAA receptor number and an uncoupling of the GABA/benzodiazepine site interactions. A single brief exposure (t1/2 = 3 min) of rat neocortical neurons to the neurotransmitter initiates a process that results in uncoupling hours later (t1/2 = 12 hr) without alterations in the number of GABAA receptors and provides a paradigm to study the uncoupling mechanism selectively. Here we report that uncoupling induced by a brief GABAA receptor activation is blocked by the coincubation with inhibitors of protein kinases A and C, indicating that the uncoupling is mediated by the activation of a phosphorylation cascade. GABA-induced uncoupling is accompanied by subunit-selective changes in the GABAA receptor mRNA levels. However, the GABA-induced downregulation of the α3 subunit mRNA level is not altered by the kinase inhibitors, suggesting that the uncoupling is the result of a posttranscriptional regulatory process. GABA exposure also produces an increase in the serine phosphorylation on the GABAA receptor γ2 subunit. Taken together, our results suggest that the GABA-induced uncoupling is mediated by a posttranscriptional mechanism involving an increase in the phosphorylation of GABAA receptors. The uncoupling of the GABAA receptor may represent a compensatory mechanism to control GABAergic neurotransmission under conditions in which receptors are persistently activated.